2017
DOI: 10.3390/nu9010082
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic and Antioxidant Response to Grape Seed, Corn and Coconut Oils in Healthy Wistar Rats

Abstract: Specialty oils differ in fatty acid, phytosterol and antioxidant content, impacting their benefits for cardiovascular health. The lipid (fatty acid, phytosterol) and antioxidant (total phenolics, radical scavenging capacity) profiles of grapeseed (GSO), corn (CO) and coconut (CNO) oils and their physiological (triacylglycerides, total and HDL-cholesterol and antioxidant capacity (FRAP) in serum and fatty acid and phytosterol hepatic deposition) and genomic (HL, LCAT, ApoA-1 and SR-BP1 mRNA hepatic levels) resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…Hepatic lipids were extracted from liver samples (1.0 g) with ice‐cold chloroform:methanol (2:1 v/v), using the Folch method (Folch, Lees, & Sloane Stanley, ). Cholesterol and fatty acids (as fatty acid methyl esters, fatty acid methyl esters) were analyzed in triplicate by gas chromatography with the same protocol used in a recent report (Wall‐Medrano et al, ), in an Agilent 6890 apparatus (Hewlett‐Packard, Wilmington, DE, USA), with an SP‐2560 capillary column (100 m × 0.25 mm; Supelco, Bellefonte, PA, USA), and a flame‐ionization detector. Values were expressed as mg/g (cholesterol), g/100 g (saturated [SFAs], monounsaturated [MUFAs], poly‐[PUFAs], and total unsaturated [UFAs] fatty acids) of total lipids, and as fatty acid ratios (MUFAs/SFAs, PUFAs/SFAs, UFAs/SFAs, n6/n3 UFAs).…”
Section: Methodsmentioning
confidence: 99%
“…Hepatic lipids were extracted from liver samples (1.0 g) with ice‐cold chloroform:methanol (2:1 v/v), using the Folch method (Folch, Lees, & Sloane Stanley, ). Cholesterol and fatty acids (as fatty acid methyl esters, fatty acid methyl esters) were analyzed in triplicate by gas chromatography with the same protocol used in a recent report (Wall‐Medrano et al, ), in an Agilent 6890 apparatus (Hewlett‐Packard, Wilmington, DE, USA), with an SP‐2560 capillary column (100 m × 0.25 mm; Supelco, Bellefonte, PA, USA), and a flame‐ionization detector. Values were expressed as mg/g (cholesterol), g/100 g (saturated [SFAs], monounsaturated [MUFAs], poly‐[PUFAs], and total unsaturated [UFAs] fatty acids) of total lipids, and as fatty acid ratios (MUFAs/SFAs, PUFAs/SFAs, UFAs/SFAs, n6/n3 UFAs).…”
Section: Methodsmentioning
confidence: 99%
“…Diets for chickens supplemented with grape seed and oil have been tested, affecting cholesterol and lipid content [ 150 ]; promising results for cholesterol transport in rats have been reported [ 151 ]. Grape seed oil supplementation in diets of animals for human consumption has been analyzed in various studies.…”
Section: Grape Seed Oil: a Novel Functional Foodmentioning
confidence: 99%
“…Some studies have also compared the effects of grape seed oils and other vegetable oils. Wall-Medrano et al [ 121 ] carried out an in vivo experiment to compare the lipids and antioxidant profile of grape seed oil, corn oil, grape seed oil, and coconut oil in healthy Wistar rats under a sub-chronic intake (28 days). They observed that rats fed with grape seed oil and corn oil had a similar deposition of total fats in the liver, which was lower than the group fed with coconut oil.…”
Section: Health Benefitsmentioning
confidence: 99%